Sport Psychology: Some new proposals being developed - Ortín-Montero, Francisco J.; Moya-Faz, Francisco; Garcés de los Fayos, Enrique J. (Anales de Psicología / Annals of Psychology, 2013)
This introduction should serve as a framework for the following monograph. While it is true that other authors have examined the discipline of sport psychology, the majority of them have done so from a very generalist perspective. For possibly the first time, there has been an attempt to rely on specialists who, from a very precise proposal, have offered us unique approaches with a wide scientific foundation applied to this area of study. A theoretical framework that adequately delimits the structure of this proposal regarding sport psychology is presented.